2023
DOI: 10.1097/cce.0000000000000946
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Administration of Vasopressors Prior to Emergency Intubation in Critically Ill Patients: A Secondary Analysis of Two Multicenter Clinical Trials

Abstract: OBJECTIVE: Hypotension affects approximately 40% of critically ill patients undergoing emergency intubation and is associated with an increased risk of death. The objective of this study was to examine the association between prophylactic vasopressor administration and the incidence of peri-intubation hypotension and other clinical outcomes. DESIGN: A secondary analysis of two multicenter randomized clinical trials. The clinical effect of prophylactic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…However, there is no definitive evidence that vasopressor use leads to rebound hypertension 23 . Fuchita et al 24 performed a propensity-matched secondary analysis of two multicenter trials on ETI in critically patients and reported that routine use of preintubation vasopressors was not associated with a lower incidence of PIH. Further studies must evaluate the role of routine vasopressor use before ETI in trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no definitive evidence that vasopressor use leads to rebound hypertension 23 . Fuchita et al 24 performed a propensity-matched secondary analysis of two multicenter trials on ETI in critically patients and reported that routine use of preintubation vasopressors was not associated with a lower incidence of PIH. Further studies must evaluate the role of routine vasopressor use before ETI in trauma patients.…”
Section: Discussionmentioning
confidence: 99%